2013
DOI: 10.1002/ijc.28442
|View full text |Cite
|
Sign up to set email alerts
|

Short report: Limited effectiveness of screening mammography in addition to clinical breast examination by trained nurse midwives in rural Jakarta, Indonesia

Abstract: Low-and middle-income countries (LMICs) are undergoing an increase in incidence of breast cancer, but have inadequate resources to implement mammographic screening. Clinical breast examination (CBE) has been suggested as an alternative to mammography in these settings. We compared the results of CBE screening by 47 midwives and 15 trained lay health workers to results of independently performed mammographic screening in an unscreened population of 1,179 women in Jakarta, Indonesia. Two hundred and eight-nine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…These issues led to early termination of the study [53]. A study of CBE and mammography in Indonesia similarly demonstrated low rates of follow-up among women actually diagnosed with cancer, with only 42.8% of those returning for treatment [54]. A report of a breast cancer awareness and screening campaign in the Democratic Republic of Congo (DRC) reported that 73% of women found to have a palpable mass never followed up for further evaluation; although not emphasized in the article, it seems that women had to pay for most of their subsequent evaluation, which presumably presented a significant barrier to follow-up as well as treatment of cancers detected [55].…”
Section: Early Detection and Screeningmentioning
confidence: 99%
“…These issues led to early termination of the study [53]. A study of CBE and mammography in Indonesia similarly demonstrated low rates of follow-up among women actually diagnosed with cancer, with only 42.8% of those returning for treatment [54]. A report of a breast cancer awareness and screening campaign in the Democratic Republic of Congo (DRC) reported that 73% of women found to have a palpable mass never followed up for further evaluation; although not emphasized in the article, it seems that women had to pay for most of their subsequent evaluation, which presumably presented a significant barrier to follow-up as well as treatment of cancers detected [55].…”
Section: Early Detection and Screeningmentioning
confidence: 99%
“…The study found that in this unscreened population of 1,179 women in which 14 cancers were found, 13 were found on clinical breast examination, confirming that screening mammography adds little to cancer detection in previously unscreened LMIC populations like that of Indonesia. 53 Scaling capacity is envisaged by future pilot or demonstration projects to validate the effect of an intervention then scaling up according to resource availability. 54 This resource stratification model for guideline development has been successfully used in a diverse spectrum of countries around the world.…”
Section: Case Study: Breast Health Global Initiativementioning
confidence: 99%
“…29-31 In promoting general breast health awareness, nurses are a well-suited professional group to destigmatize disease within their respective communities. 11 Nurses in LMICs knowledgeable about breast health and with skills in clinical breast examination can contribute to reaching the goal of downstaging the presentation of breast cancer in these countries.…”
Section: Nursing’s Potential Contributions To Cancer Care: What Can Bmentioning
confidence: 99%